The properties of optical lightning flashes and the clouds they illuminate. Issue 1 (13th January 2017) - Peterson, Michael; Deierling, Wiebke; Liu, Chuntao; Mach, Douglas; Kalb, Christina
Abstract: Optical lightning sensors like the Optical Transient Detector and Lightning Imaging Sensor (LIS) measure total lightning across large swaths of the globe with high detection efficiency. With two upcoming missions that employ these sensors—LIS on the International Space Station and the Geostationary Lightning Mapper on the GOES‐R satellite—there has been increased interest in what these measurements can reveal about lightning and thunderstorms in addition to total flash activity. Optical lightning imagers are capable of observing the characteristics of individual flashes that include their sizes, durations, and radiative energies. However, it is important to exercise caution when interpreting trends in optical flash measurements because they can be affected by the scene. This study uses coincident measurements from the Tropical Rainfall Measuring Mission (TRMM) satellite to examine the properties of LIS flashes and the surrounding cloud regions they illuminate. These combined measurements are used to assess to what extent optical flash characteristics can be used to make inferences about flash structure and energetics. Clouds illuminated by lightning over land and ocean regions that are otherwise similar based on TRMM measurements are identified. Even when LIS flashes occur in similar clouds and background radiances, oceanic flashes are still shown to be larger, brighter, longer lasting, more prone to horizontal propagation, and to contain more groups than their land‐based counterparts. This suggests that the optical trends noted in literature are not entirely the result of radiative transfer effects but rather stem from physical differences in the flashes. Key Points: Optical lightning measurements can be used to identify propagating flashes Flash characteristics are sensitive to cloud properties that affect scattering Oceanic flashes are still larger and more energetic when they occur in similar cloud regions as their land‐based counterparts